2000
DOI: 10.1002/(sici)1097-4628(20000523)76:8<1248::aid-app5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Determining the gel point of an epoxy-hexaanhydro-4-methylphthalic anhydride (MHHPA) system

Abstract: ABSTRACT:The DEBGA-MHHPA epoxy system has found increasing applications in microelectronics packaging for which the ability to understand and model the cure kinetics mechanism accurately is crucial. The present article reports on the work done to elucidate accurate knowledge of the gel point by rheological methods. To determine the gel point using the GЈ-GЉ crossover method was found not to be accurate, and the gel point obtained by this method was found to be frequency-dependent. Using the point where tg␦ was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…The critical exponent D therefore, assumes a high level of importance in understanding the formation of the gelled material as it provides a framework to understand the dynamic mechanical properties of a polymer structure at gelation. The value of D determined for a wide range of epoxy amine networks has been shown to be consistently around 0.70, [38,39] although Scanlon and Winter showed that it is not a universal constant and is dependent upon precursor composition. Other polymer systems have been shown to produce values ranging from 0.2 to 0.70.…”
Section: Network Formationmentioning
confidence: 99%
“…The critical exponent D therefore, assumes a high level of importance in understanding the formation of the gelled material as it provides a framework to understand the dynamic mechanical properties of a polymer structure at gelation. The value of D determined for a wide range of epoxy amine networks has been shown to be consistently around 0.70, [38,39] although Scanlon and Winter showed that it is not a universal constant and is dependent upon precursor composition. Other polymer systems have been shown to produce values ranging from 0.2 to 0.70.…”
Section: Network Formationmentioning
confidence: 99%
“…Accurate knowledge on the gelation time would therefore allow the estimation of the optimal temperature and time for which the sample should be heated before being allowed to set in the mold. 31 It was found that the application of the G 0 -G 00 crossover method for gelation point determination is only effectively suitable for some specific polymers as given by the Winter's criterion. 32 Mehran Hayaty has reported that the crossover of G 0 and G 00 of the EP system does not occur at the frequency ranges.…”
Section: Resultsmentioning
confidence: 99%
“…The gel point in rheological experiments is determined using various methods, according to different definitions [42,43]: the divergence point or fixed level of the viscosity [44,45], the crossover point of the dynamic storage modulus (G') and loss modulus (G") [46], or the point at which the loss tangent becomes independent of testing frequency [47][48][49][50]. The gel point for NPU-2d, as the crossover point of G' and G" appears at 116.5°C as can be seen in Figure 8a.…”
Section: Rheological Behaviourmentioning
confidence: 99%